Using mobile apps in teaching vocabulary in EFL classrooms - Zamira Akromjonovna, Akromjonova; Radjabova , Gulnoza Giyosiddinovna (The Lingua Spectrum, 2026)
Mobile apps have really changed how people learn languages, especially for English as a foreign language, which means that with phones everywhere, it has become easier than ever to learn new words outside of class. This paper is aimed to explore different apps that help with vocabulary acquisition, like those spaced repetition ones or games that make it fun. It is based on studies on mobile learning and compares them to old school methods. Apps seem to boost motivation and help remember words better, but there are issues too, like getting tired of screens or not everyone having good internet. In the end, mixing apps with regular teaching could make a big difference for EFL students.